1964
DOI: 10.1111/j.1365-2494.1964.tb01188.x
|View full text |Cite
|
Sign up to set email alerts
|

THE DIGESTIBILITY OF THE LEAVES AND STEMS OF PERENNIAL RYEGRASS, COCKSFOOT, TIMOTHY, TALL FESCUE, LUCERNE AND SAINFOIN, AS MEASURED BY AN IN VITRO PROCEDURE

Abstract: Determinations of the in vitro digestibilities of leaf-blade, leaf-sheath and stem fractions of the grasses cocksfoot, perennial ryegrass, timothy and tall fescue and of the leaves and stems of lucerne and sainfoin have shown that all parts of the plant have a high digestibility at early stages of growth. With increasing maturity, however, the digestibility of the stem falls olT at a much faster rate than that of the leaf; in grasses, leaf-sheath digestibility declines at an intermediate rate. The decline of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
138
4
7

Year Published

1982
1982
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(166 citation statements)
references
References 11 publications
17
138
4
7
Order By: Relevance
“…However, the rate of decline in IVTD and IVCWD, and the rate of increase in NDF concentration was much greater for stems than leaves. These results agree with those of Terry and Tilley (1964) and Mowat et al (1965) on in vitro digestibility of dry matter, and with those of Sanderson and Wedin (1989) on in vitro digestibility and NDF concentration. The results of Mowat et al (1965) also indicated that the digestibilities of both leaves and stems of earlymaturing cultivars on a given date were less than those of late-maturing cultivars.…”
Section: Results and Discussion Relationship Of Nutritive Value With supporting
confidence: 82%
“…However, the rate of decline in IVTD and IVCWD, and the rate of increase in NDF concentration was much greater for stems than leaves. These results agree with those of Terry and Tilley (1964) and Mowat et al (1965) on in vitro digestibility of dry matter, and with those of Sanderson and Wedin (1989) on in vitro digestibility and NDF concentration. The results of Mowat et al (1965) also indicated that the digestibilities of both leaves and stems of earlymaturing cultivars on a given date were less than those of late-maturing cultivars.…”
Section: Results and Discussion Relationship Of Nutritive Value With supporting
confidence: 82%
“…Bite rate was significantly higher on Aries HD than on Yatsyn 1 pasture, perhaps reflecting the higher proportion of ryegrass leaf in this spring pasture (Table 4). The digestibility of ryegrass stem declines at a much faster rate than that of the leaf (Terry & Tilley 1964). However, the greater leaf content of Aries HD ryegrass in this study was not reflected in higher digestibility of either whole sward, plucked samples, or oesophagealfistulated sheep samples.…”
Section: Discussioncontrasting
confidence: 43%
“…As pseudostem is a collection of leaf sheaths rolled together (Robson et al, 1988), it is more digestible than true stem. Evidence suggests that during vegetative growth, the digestibility of pseudostem is not significantly reduced compared with the leaf blade (Terry and Tilley, 1964), offering further explanation for the absence of a relationship between sward structure and chemical composition during the vegetative growth phase.…”
Section: Sward Chemical Compositionmentioning
confidence: 97%
“…The values are comparable with those reported by Smit et al (2005b) (86.9%) and Gowen et al (2003) (84.7%). The OMD concentration of the leaf is higher than that of stem or dead material (Terry and Tilley, 1964;Hacker and Minson, 1981); a 5.5% change in leaf content is equal to a 1% change in digestibility (Stakelum and O'Donovan, 1998). During the reproductive growth phase of the current study, a 1% change in digestibility was brought about by a 3.1% change in leaf proportion.…”
Section: Sward Chemical Compositionmentioning
confidence: 99%